Knowledge and Practice on Birth Preparedness and Complication Readiness among Pregnant Women in Selected Ward of Biratnager Municipality, Nepal - Subedi, Sabitra (Tribhuvan University Journal, 2019)
Birth preparedness and complication readiness is the process planning for normal birth and anticipating the action needed in case of an emergency. Promoting birth and emergency planning helps to improve preventive behavior, increase awareness of mothers about danger signs and improvement in care seeking behavior in the case of obstetric complication. A cross sectional descriptive quantitative community-based study was conducted to assess knowledge and practice on birth preparedness and complication readiness among 150 pregnant women of 24 weeks gestation and above in selected wards of Biratnagar with non- probability purposive sampling.The findings of the study showed that 22.7% of the respondents had adequate knowledge on the birth preparedness and complication readiness and 19.8% of respondents had adequate practice. However, the only 9.3% of respondents were prepared for birth complications. Analysis using chi square test identified statistically significant association between knowledge and practice. The study found significant association of knowledge with gravida and weeks of gestation. It seemed there is significant association of practice level with occupation and weeks of gestation and weeks of gestation. The study identified inadequate knowledge and practices on birth preparedness and complication readiness. Thus, the government office, policy makers and partner that are working in maternal health should give due emphasis to preparation for birth and its complication and provide information and education to all pregnant women at community level.